Case Report: Technetium-99m Pertechnetate Scintigraphy Findings in a Dog With Iodine Deficiency-Induced Goitrous Hypothyroidism - Yun, Taesik; Na, Yejin; Lee, Dohee; Koo, Yoonhoi; Chae, Yeon; Nam, Hyeyeon; Kang, Byeong-Teck; Yang, Mhan-Pyo; Kim, Hakhyun (Frontiers in Veterinary Science, 2022)
There is only one previous report of canine goitrous hypothyroidism caused by iodine deficiency from 1986. The present case report describes the novel diagnostic methods and long-term outcomes of a dog diagnosed with goitrous hypothyroidism caused by iodine deficiency. A 4-year-old neutered, female Pomeranian dog presented with a cervical mass, lethargy, and inactivity. The dog had a history of eating home-cooked diets sold by a private seller for 1 year. The physical examination and ultrasonography showed two bilaterally symmetric masses in the mid-cervical area (left, 1.8 × 1.4 cm; right, 2.3 × 1.8 cm), and they were suspected to be the thyroid glands. To identify the function of the thyroid gland, the basal concentrations of thyroid hormones [total T4 (tT4) and thyroid-stimulating hormone (TSH)] were measured and a TSH stimulation test was performed: baseline tT4, 0.5 μg/dL (reference interval, 1–4 μg/dL), baseline TSH, 0.81 μg/dL (reference interval, 0.05–0.42 μg/dL), and post-tT4, 1 μg/dL (6 h after the injection of TSH). The values indicated primary hypothyroidism. The urinary iodine concentration was 302 μg/L, which was markedly lower than that of normal dogs (1,289 μg/L). Thyroid scintigraphy with technetium-99m pertechnetate was also performed to quantify the activity of the thyroid gland, and the thyroid-to-salivary ratio was 3.35. Based on the results of these examinations and patient history, the dog was diagnosed with diet-induced (iodine deficiency) goitrous hypothyroidism. The dog was treated with iodine (62.5 μg/day). At 31 days after treatment, clinical signs and thyroid hormones were normalized (tT4, 1.3 μg/dL; TSH, 0.24 μg/dL). One year after treatment, the dog was well with normal concentrations of thyroid hormones (tT4, 1.8 μg/dL; TSH, 0.27 μg/dL) and a partially reduced goiter (left, 1.6 × 1.1 cm; right, 1.2 × 0.9 cm). This is the first case to describe novel diagnostic methods and long-term outcomes of a dog diagnosed with goitrous hypothyroidism caused by iodine deficiency.